2018
DOI: 10.1016/j.ijfoodmicro.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial residues and resistance against critically important antimicrobials in non-typhoidal Salmonella from meat sold at wet markets and supermarkets in Vietnam

Abstract: A B S T R A C TExcessive antimicrobial usage and deficiencies in hygiene in meat production systems may result in undesirable human health hazards, such as the presence of antimicrobial drug residues and non-typhoidal Salmonella (NTS), including antimicrobial resistant (AMR) NTS. Recently, Vietnam has witnessed the emergence of integrated intensive animal production systems, coexisting with more traditional, locally-sourced wet markets. To date no systematic studies have been carried out to compare health haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
72
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 40 publications
12
72
3
2
Order By: Relevance
“…The prevalence of Salmonella in minced meat has been reported up to 12 percent by [41] which indicates high microbiological risk because Salmonella must not be present in meat when it is sold. Similar results have also been reported by [42]. Some research studies have reported 5%-20% prevalence of Salmonella in meat [43,44].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence of Salmonella in minced meat has been reported up to 12 percent by [41] which indicates high microbiological risk because Salmonella must not be present in meat when it is sold. Similar results have also been reported by [42]. Some research studies have reported 5%-20% prevalence of Salmonella in meat [43,44].…”
Section: Discussionsupporting
confidence: 89%
“…There are few reports describing the prevalence of S. Pullorum in beef and other meats i.e., fish, pork etc. [42].…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of Salmonella contamination strongly suggests shortcomings in hygiene practices in retail stores, for example, storage temperature, packaging and/or holding time, all of which are important factors in Salmonella multiplication (Patchanee et al, ; Soltan Dallal, Sharifi Yazdi, Mirzaei, & Kalantar, ). Together, these factors increase the opportunity for Salmonella growth in fresh markets, resulting in a higher prevalence of Salmonella contamination than in other retail outlets (Murugadas et al, ; Nhung et al, ; Wong, Nicol, Cook, & MacDiarmid, ). Meats sold retail at supermarkets were in seal packages and stored on shelves at approximately 4°C at all times, leading to the lowest incidence of Salmonella contamination (50.00%, 95% CI: 21.71–78.29).…”
Section: Discussionmentioning
confidence: 99%
“…Together, these factors increase the opportunity for Salmonella growth in fresh markets, resulting in a higher prevalence of Salmonella contamination than in other retail outlets (Murugadas et al, 2015;Nhung et al, 2018;Wong, Nicol, Cook, & MacDiarmid, 2007). Meats sold retail at supermarkets were in seal packages and stored on shelves at approximately 4°C at all times, leading to the lowest incidence of Salmonella contamination (50.00%, 95% CI: 21.71-78.29).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, marketed perishable foods have high rates of microbiological and chemical contamination, with the most serious issues related to meat. For example, in a recent study, Nguyen and others (2018) found the presence of non-typhoidal Salmonella-a leading source of foodborne diseases for nearly 900,000 illnesses annually-in 71 percent of chicken samples taken in Hanoi and HCMC. The Salmonella prevalence rate was higher in wet markets (90 percent) than in supermarkets (53 percent).…”
Section: The Consequences Of Poor Connectivity and Practicesmentioning
confidence: 99%